Qualidade das informações sobre aleitamento materno e alimentação complementar em sites brasileiros de profissionais de saúde disponíveis na internet The quality of information on maternal breast feeding and complementary feeding on Brazilian internet sites available for health professionals - Rosângela Quirino da Silva; Muriel Bauermann Gubert (Instituto Materno Infantil de Pernambuco, 2010)
OBJETIVOS: analisar as informações de sites da internet sobre o aleitamento materno e alimentação complementar de acordo com a adequação às recomendações do Ministério da Saúde do Brasil. MÉTODOS: realizado estudo transversal, com amostra de 103 sites de profissionais de saúde. Analisaram-se informações sobre aleitamento materno (AM) e alimentação complementar (AC). As informações foram quantificadas e analisadas qualitativamente. RESULTADOS: as recomendações relativas ao AM foram: exclusivo até 6º mês (64,1%); sem água e chá (31,1%); duração de dois anos ou mais (36,9%); e não utilizar mamadeira e chupeta (33%). Para a AC foi utilizada a terminologia desmame (30,1%), recomendada a introdução alimentar no 6º mês (47,9%), introdução da primeira papa com fruta (11,6%) ou suco (9,7%); e a oferta de sopa (14,6%) como refeição. Na análise qualitativa, entre as informações incorretas, constavam recomendações de consumo de carne no 12º mês, horários regulares para refeições, introdução de alimentos no 7º mês e consumo de leite de vaca no 6º mês. CONCLUSÕES: a maior parte das informações sobre aleitamento materno está de acordo com o preconizado pelo Ministério da Saúde, mas são insuficientes para estimular a prática do aleitamento materno. Já as informações sobre alimentação complementar na sua maioria divergem do recomendado. OBJECTIVES: to analyze the information available on internet sites regarding maternal breast feeding and complementary feeding according to the recommendations of the Brazilian Ministry of Health. METHODS: a cross-sectional study was carried out using a sample of 103 sites for professional healthcare workers. Information was analyzed on maternal breast feeding (MB) and complementary feeding (CF). The information was quantified and analyzed qualitatively. RESULTS: the recommendations for MB were: that it should be exclusive up to the 6th month of life (64.1%); that no water or tea should be added (31.1%); that it should last for two years or more (36.9%); and that bottles and/or pacifiers should not be used (33%). For CF, the term weaning was used (30.1%), it was recommended that solid feeding begin in the 6th month of life (47.9%), involving fruit pulp (11.6%) or juice (9.7%); and soup (14.6%). According to the qualitative analysis, incorrect information included recommending the consumption of meat in the 12th month of life, regular meals, the introduction of solid food in the 7th month and the consumption of cow's milk in the 6th month. CONCLUSIONS: most of the information on breast feeding accords with the advice of the Brazilian Ministry of Health, but is not sufficient to encourage breast feeding. The information on complementary feeding mostly diverges from the official recommendations.